MAKNA KERJA DALAM AJARAN SOSIAL GEREJA Ditinjau Dari Perspektif Ensiklik Laborem Exercens Dan Ensiklik Rerum Novarum - Pranyoto, Yohanes Hendro (SEPAKAT-Jurnal Pastoral Kateketik, 2017)
Everyone has to work. By working, people can sustain their life and they alsochange the face of the world. In some points, everyone has different meaningsabout work. This writing wants to describe the true meaning of work accordingto the teachings of the Church. This writing uses library research type. Theprimary data source in this paper consists of two documents (Encyclical)namely Encyclical Laborem Exercens by Pope John Paul II and EncyclicalRerum Novarum written by Pope Leo XIII. In these two encyclicals, theessential meaning of work is the activity that man undertakes to sustainand develop his life. The call to work also shows that humans as partners ofGodâs work to develop the world. As Godâs working partner, the archetype ofhuman labor is adapted to Godâs actions in the world: creating, nurturing andimproving.